On the Antiquity of the Virginity Blessing - Yahalom, Shalem (Zutot, 2024)
A variety of sources support the claim that different versions of the virginity blessing were recited throughout the Jewish communities during the Middle Ages. Despite its widespread use, the virginity blessing and confirmation ritual are not mentioned in the Talmud, and the wording of the blessing is first mentioned only in Sefer Halakhot gedolot. The absence of this blessing in earlier texts can be considered from two alternative perspectives. The first is that the blessing was composed after the Mishnah and Talmud were canonized. Alternatively, it was indeed an early blessing, but it was practiced in circles that operated outside the scholarly mainstream. Ruth Langer preferred the second possibility. This study will adopt Langer’s position that the blessing originated in the Land of Israel. It will show, however, that this blessing could not have been recited in ancient times and that it must have been a later development.